EFFECT OF PROCESS PARAMETERS FOR OPTIMUM MATERIAL REMOVAL RATE OF CYLINDRICAL GRINDING OF AISI 1045 STEEL - Singh, Taranveer; Goyal, Khushdeep; Kumar, Parlad (Journal of Mechanical Engineering, 2015)
In this experimental work, the effect of various input parameters viz. work speed, wheel speed,abrasive material, depth of cut, concentration of cutting fluid and number of passes has been studied on thematerial removal rate of cylindrical grinded AISI. For experimentation, three levels of each variable have beenselected except wheel speed. Two levels of wheel speed have been taken. Heat treated AISI 1045 has beenconsidered as work piece material. The result reveals that number of passes followed by the type of abrasivematerial is the most significant to influence material removal rate. The optimum set of input parameters formaximizing the material removal rate has also been found.